PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Assri Nuur Tri Oktafiyanti; Rika syahadatina (Universitas Prof. Dr. Hazairin SH, 2021)
This study aims to examine the effect of the corporate governance mechanism consisting of:managerial ownership, institutional ownership, and audit committee, on the timeliness offinancial reporting. This research is a quantitative descriptive study. The population used bythe researcher is a manufacturing company in the consumer goods industry sector and thebasic and chemical industry sector. The sample used is purposive sampling, which is asample selected from the population with certain criteria so that the financial statements of30 manufacturing companies are obtained. The test results show that all variables have asignificant effect both simultaneously and partially, namely the managerial ownershipvariable shows significant results, meaning that managerial ownership affects the timelinessof financial reporting. Institutional ownership variable shows significant results, meaningthat institutional ownership affects the timeliness of financial reporting. The audit committeevariable shows significant results, meaning that the audit committee has a significant effecton the timeliness of financial reporting. Meanwhile, the simultaneous test shows significantresults, which means that Managerial Ownership, Institutional Ownership, and the AuditCommittee have a significant effect on the timeliness of financial reporting. The limitations ofthis study are the lack of a broad research area in manufacturing and only focusing on a fewsectors in manufacturing companies, this research can be a reference for companies toimprove Corporate Governance Mechanisms so that companies become more developed.